Condition Factor and Length-Weight Relationship of Labeo victorianus (Boulenger, 1901) in the Selected Rivers of the Lake Victoria Basin, Kenya - Nakangu, N. F.; Barasa, J. E.; Matolla, G. K.; Riziki, J. W.; Mbalassa, M.; Masese, F. O. (Africa Environmental Review Journal, 2021)
We studied the length‐weight relationship (LWR) and condition factor of Labeo victorianus (Boulanger, 1901) in four rivers (Awach, Mara, Nyando and Sondu-Miriu) in Lake Victoria Basin, Kenya. A total of 421 fish individuals of the species were measured for length and weighed. There was no significant variation in mean relative condition (Kn) of L. victorianus (ANOVA F= 0.54, df=3, p=0.65) in the rivers. The species from Mara and Sondu Miriu showed positive allometric growth while those from Awach and Nyando rivers showed negative allometric growth. The lowest mean condition factor K was recorded for females in the Mara and Nyando rivers (0.975 and 0.872 respectively). The length (ANOVA F=64.20, df=3, p<0.001) and weight (ANOVA F= 25.56, df=3, p< 0.001) were significantly different in Mara River. The relative condition factor showed significant variation with the total length (p<0.0001 and VIF <1). Variations in the length-weight relationship indicates the degree of environmental degradation to which the fish species is subjected to in the rivers of the LVB. This study recommends that environmental management should be considered as one of the strategies for conserving this and other threatened species in the LVB.